Pengaruh Iklan Dan Harga Terhadap Keputusan Pembelian Konsumen Telepon Pintar Merek Xiaomi Di Plaza Medan Fair - Situmorang, Flora Nikita; Sianturi, Charles M.; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
The purpose of this study is to measure the influence of Advertising, Price and Consumer Purchasing Decisions of Xiaomi Palaza Medan Fair Smartphones. This study uses a quantitative method with nonprobability sampling techniques and a purposive sampling approach with a sample of 97 respondents. The data collection technique is carried out by distributing questionnaires to consumers with the purchase of the last Xiaomi smartphone. The data were analyzed using multiple regression analysis which began with validity, reliability, classical assumptions, determination coefficients, F test and t test conducted using SPSS statistic version 25. Based on the partial t test and the F test simultaneously, it was shown that three independent variables Advertising and Prices had a positive and significant effect on the purchase decision by consumers at Plaza Medab Fair. Based on the determination coefficient R2, it can be seen that two independent variables explain the 0.483%, the variability of Xiaomi product purchase data and the remainder can be explained by other variables that were not studied in this research.